(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
This paper to study on commercial large-scale mining in Mongolia that how to impact on the economy. During the last few years, the mining sectors were started to provide an important contribution in GDP. The mining sector is a major contributor to Mongolia economy, accounting for about 17% of GDP, 65% of industrial value added and 58% of export earnings. Hovewer, over than 12,000 people working in mining sector, and the informal (artisanal) mining sector involves many times this number. This study examined the mining-in related-migration and impact on the economy. The study was optioned from major mining companies of Mongolia. This results were analyzed by using Excel and Software.